Alliances rebalanced?: The social meaning of the U.S. pivot and allies’ responses in northeast Asia - Harnisch, Sebastian; Friedrichs, Gordon (The Korean journal of international studies, 2016)
Sebastian Harnisch and Gordon Friedrichs. KJIS 2017;15:1-39. https://doi.org/10.14731/kjis.2017.04.15.1.1